Back Cover: Advanced Engineering Materials 4∕2014. Issue 4 (April 2014) - Unknown
<x xml:space="preserve">Abstract</x> The cover graphic shows the scheme of the possible growth mechanism of two kinds of ZnSe‐based longitudinal twinning nanowires grown by a simple thermal evaporation method. More details can be found in the article by Chunrui Wang and co‐workers on page 459. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>